Transformation of Urban Social Interaction in the Era of Artificial Intelligence and Digital Society - Ahmad Mubarok; Rosmaria Rosmaria (PT. AVID MEDIA INDONESIA, 2026)
The rapid integration of artificial intelligence (AI) and digital technologies into everyday urban life has fundamentally reshaped the patterns, quality, and dynamics of social interaction in urban communities. This study examined the transformation of social interaction among urban populations in Indonesia amid the proliferation of AI-driven platforms, smart city infrastructure, and digital communication systems. A mixed-methods approach was employed, combining a quantitative survey of 480 urban residents across five Indonesian cities with qualitative interviews involving 32 key informants. Social interaction transformation was assessed across five dimensions: communication modality, social trust, community cohesion, digital inclusion, and civic participation. Results indicate a significant shift toward digitally mediated social interaction, with 68.7% of respondents reporting that online interaction has become their primary mode of daily communication. AI-enabled platforms significantly predicted urban social cohesion (β=0.521, p<0.001), while digital literacy moderated the relationship between AI adoption and positive social outcomes. Alarming disparities were identified between high-income metropolitan areas and lower-income urban peripheries, reflecting a persistent digital divide that exacerbates social inequality. The metaverse, algorithmic governance, and AI chatbots emerged as novel interaction environments that simultaneously democratize and fragment social engagement. These findings contribute to an emerging theoretical framework positioning digital transformation as an interaction-driven nexus between society, technology, and urban governance.